Profil Biokimia Darah Akibat Pemberian Ekstrak Akar Burdock (Arctium lappa L.) pada Tikus Putih (Rattus norvegicus) - Ika Aulia Fazrianti; Dini Puspodewi; Imam Agus Faizal (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Burdock (Arctium lappa L.) is a medicinal plant that contains active compounds such as flavonoids, lignans, and phenolic acids, which act as antioxidants, anti-inflammatory agents, and hepatoprotective substances. This study aimed to evaluate the blood biochemical profile following the administration of burdock root extract in white rats (Rattus norvegicus). The study was conducted experimentally using eight male and female rats, divided into four groups: a negative control group (aquadest) and three treatment groups receiving doses of 150, 300, and 450 mg/kgBB orally for 28 days. Blood biochemical parameters were examined on day 36, including albumin, total protein, globulin, glucose, urea, amylase, cholesterol, ALT, ALP, total bilirubin, creatinine, and creatine kinase. The results showed that most biochemical parameters remained within the normal range, although significant changes were observed in some groups. Urea, amylase, and total bilirubin levels remained stable, while total protein, globulin, and ALP levels tended to be higher in female rats. Elevated glucose, cholesterol, and ALT levels in most treatment groups indicated potential disturbances in carbohydrate and lipid metabolism, while increased creatinine levels in some groups suggested possible nephrotoxic effects. Administration of burdock root extract influenced the biochemical blood profile, particularly related to glucose and lipid metabolism as well as liver function. Further studies are needed to explore the underlying mechanisms and evaluate the long-term safety of burdock root extract.